Elemental composition of salt and vulnerability assessment of saline groundwater sources selected based on ethnoarchaeological evidence in Romania - Mihu-Pintilie, Alin; Vasilache, Viorica; Tencariu, Felix-Adrian; Asăndulesei, Andrei (Frontiers in Earth Science, 2023)
The study aimed to evaluate the elemental composition of salt extracted from shallow to saline groundwater sources selected based on ethnoarchaeological evidence in the Eastern Carpathians and Sub-Carpathians area of Romania and to assess their specific vulnerability using groundwater pollution potential (DRASTIC and DRASTIC-LU methodology). 198 saline water samples were collected from different site types, including natural saline springs, catchment saline springs, brine wells, salted lakes and ponds, during the period between 2007 and 2019. Scanning electron microscopy with energy-dispersive X-ray spectroscopy was employed to characterize the elemental composition of salt after dry-evaporating a predetermined volume of each collected sample. The results indicated that the salt concentration in the brines ranged from 0.1% to 41.3%, with the highest concentration found in wells and natural saline springs. The dominant component was sodium chloride, but several sites had high concentrations of potassium chloride, which is essential for human health. Over 95% of the analyzed samples also contained other minerals like calcium and magnesium, further highlighting the health benefits of these brine sources. However, two sites were slightly contaminated with heavy metals, posing potential health risks if consumed. The DRASTIC index, a standardized system for evaluating groundwater pollution potential, gave scores between 99 and 208, indicating moderate to very high intrinsic pollution potential. Similarly, the DRASTIC-LU index, which takes into account and the land use aspects, showed scores ranging from 114 to 258, suggesting low to very high vulnerability to contamination. These findings provide valuable information on the elemental composition of salt and the vulnerability of these brine sources, which are still used by rural communities for traditional practices like meat and fish preservation, milk curdling, and pickling. The study has important implications for sustainable management from both ethnoarchaeological and economic perspectives.